Wabah dan Peringatan Perjalanan dalam Persepsi Wisatawan - Nur Hakim, Imam (Jurnal Master Pariwisata (JUMPA), 2020)
Travel risk factors are always becoming tourist considerations to make decisions. The most important travel risks are health problems and the disease that exist in the destination. That existence often affects the perception of tourists. This perception is also exacerbated by the emergence of travel warnings issued by related institutions. Thus, perceptions of travel risks and travel warnings simultaneously influence travelers' decisions. Using a descriptive qualitative approach through a literature review, this study found several internal and external indicators that influence tourist perceptions of disease, as well as indicators that influence their perception of travel warnings as an emphasis on the current situation that occurs in affected tourist destinations. These indicators need to be considered as an effort to respond and restore the situation if Indonesia is later affected by a disease and travel warnings. Keywords:   Disease, Travel Warnings, Travel Risk, Tourism